Impacts of different objective functions on resource leveling in Line-of-Balance scheduling - Damci, Atilla; Arditi, David; Polat, Gul (Elsevier BV, 2016)
This study investigates the impacts of using different objective functions in leveling resources in schedules established by using Line-Of-Balance (LOB) methodology. A genetic algorithm-based model that considers different objective functions was used for leveling resources in LOB schedules. This model uses the principles of “optimum crew size” and “natural rhythm” that assume that the highest productivity can be achieved as long as an activity is performed in a unit of production by one or multiple crews of optimum size. Therefore, one needs to change the number of crews employed to shift the start times of an activity forwards or backwards at different units of production. The total project duration, the duration of an activity in any unit and the precedence relationships between activities remain the same during this procedure. Two LOB schedules are established for a pipeline project and are used to investigate the impacts of using different objective functions for resource leveling in LOB. It was observed that the objective functions provided the same optimal resource distribution. However, prudent schedulers should consider all ten objective functions because the distribution of resources depends on the number of activities, the float of each activity, and the precedence relationships between activities.